The utilization of active methodologies in nursing education: the perception of undergraduate course students - dos Santos, Victoria Marina Lima; Santos, Ione Ferreira; Hamamoto, Cássia Galli; Chirelli, Mara Quaglio (Multi-Science Journal, 2020)
The objective of this research is to analyze how nursing students of the Marilia Medical School (FAMEMA) perceive the Systematized Educational Unit, to motivate the reflection regarding the course’s curriculum, which goes through a dynamic improvement process, allowing the implementation of necessary changes. It’s about a qualitative study, in which 20 undergraduates from the first and second years were interviewed, providing data for the thematic analysis. The chosen analysis modality made possible to explore the object of investigation in a systematic way and contributed to the beginner’s researcher learning about the qualitative data process. Through the thematic analysis it was observed, in the undergraduates speeches, some contributions of the active methodologies: the learning how to learn, the development of the critical reasoning and the autonomy to search for information in a qualified way, to build the knowledge, teamwork abilities and the humanized education focused on the broader approach of the care. The articulation of the tutorial cases with practice is considered a strength by the interviewed, while the undergraduates’ difficulty in transitioning from the traditional teaching method to the active methodologies after they enroll in FAMEMA is a weakness. According to the students, the study is deeper in the active methods of teaching-learning compared to the traditional teaching. However, there is a need to improve how the contents are delimited and explored.